Effects of different rootstocks on aroma volatile constituents in the fruits of peach (Prunus persica L. Batsch cv. 'Cresthaven'). Issue 1 (2nd January 2017) - Seker, M.; Ekinci, N.; Gür, E.
ABSTRACT: The consumption of peaches is dependent on fruit quality. Aromatic compounds directly affect the sensorial quality and consumer acceptance of peaches. This study evaluated the fruit quality and aroma volatile constituents of the peach cultivar 'Cresthaven' grafted on to five different rootstocks in 2012 and 2013. The rootstocks used were 'Uzunoglu Seedling' ( Prunus persica ), 'GF677' ( P. persica × P. dulcis ), 'Nemaguard' ( P. persica × P. davidiana ), 'Cadaman' ( P. persica × P. davidiana ) and 'St. Julien GF 655/2' ( P. insititia ). Fruits were sampled at the commercial maturity stage around mid-August. Fruit quality characteristics and aroma volatiles differed significantly in peaches grown on different rootstocks. The largest fruits and highest titratable acidity were obtained from 'Cadaman'. The major volatile constituents of 'Cresthaven' fruits were acetaldehyde, hexanal, benzaldehyde, ethanol, 1-hexanol, (Z)-3-hexenol, (E)-2-hexen-1-ol, linalool, ethyl acetate, hexyl acetate, (Z)-3-hexenyl acetate, (E)-2-hexenyl acetate, 6-methyl-5-hepten-2-one, (E)-β-ionone, γ-decalactone and limonene. The type and concentration of volatile compounds showed great variability in 'Cresthaven' peach grafted on to different rootstocks. A total of 91 volatile compounds were detected and the highest volatile content was found in 'GF677'.